2000
DOI: 10.1161/01.cir.102.25.3104
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Endothelial Nitric Oxide Production After Withdrawal of Statin Treatment Is Mediated by Negative Feedback Regulation of Rho GTPase Gene Transcription

Abstract: Withdrawal of statin therapy in normocholesterolemic mice results in a transient increase of rho activity, causing a suppression of endothelial NO production. The underlying molecular mechanism is a negative feedback regulation of rho gene transcription mediated by the actin cytoskeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
182
2
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 239 publications
(201 citation statements)
references
References 31 publications
11
182
2
6
Order By: Relevance
“…20 Animal studies have demonstrated that the short-term withdrawal of statin therapy leads to a profound rebound phenomenon with impaired NO bioavailability. 21 Consistently, a recent study in patients with stable coronary heart disease showed a 3-fold increase in thrombotic vascular events after simvastatin treatment was stopped and continued with relatively lower doses of fluvastatin. 22 To test the hypothesis that the discontinuation of statin therapy has an adverse impact on patients with acute coronary syndromes, we performed the present subgroup analysis by using the data set of the Platelet Receptor Inhibition in Ischemic Syndrome Management (PRISM) trial.…”
mentioning
confidence: 72%
“…20 Animal studies have demonstrated that the short-term withdrawal of statin therapy leads to a profound rebound phenomenon with impaired NO bioavailability. 21 Consistently, a recent study in patients with stable coronary heart disease showed a 3-fold increase in thrombotic vascular events after simvastatin treatment was stopped and continued with relatively lower doses of fluvastatin. 22 To test the hypothesis that the discontinuation of statin therapy has an adverse impact on patients with acute coronary syndromes, we performed the present subgroup analysis by using the data set of the Platelet Receptor Inhibition in Ischemic Syndrome Management (PRISM) trial.…”
mentioning
confidence: 72%
“…2 Moreover, due to the association of cardiovascular risk factors and cardiovascular diseases with ED, prevalence of ED rises up to 50-75% in cardiovascular high-risk patients, depending on the method of evaluation used. 3,17,18 Patients suffering from the metabolic syndrome, including risk factors like hypertension, insulin resistance, obesity and dyslipidemia are considered to be predisposed to develop cardiovascular diseases, which contributes to the incremental role of the metabolic syndrome in health economics, especially in the industrialized Western countries. 19 The present study demonstrates a high prevalence of ED in hypertensive patients with the metabolic syndrome, who represent a cardiovascular high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Because three-dimensional colocalization of intracellular proteins is regulated by cytoskeletal rearrangements, changes in statin-induced actin cytoskeleton could affect intracellular transport, membrane trafficking, mRNA stability and gene transcription. Indeed, statins have been reported to cause alterations in the actin cytoskeleton and the assembly of focal adhesion complexes by inhibiting RhoA and Rac1 isoprenylation [41].…”
Section: Other Small Gtpasesmentioning
confidence: 99%